Neuromuscular synergy characteristics of Tai Chi leg stirrup movements: optimal coordination patterns throughout various phases - Zhang, Xiaopei; Jia, Mengyao; Ke, Yong; Zhou, Jihe (Frontiers in Bioengineering and Biotechnology, 2024)
The Tai Chi Leg Stirrup Movement is one of the most challenging leg techniques, requiring athletes to maintain overall balance while rapidly and accurately mobilizing muscles. However, in-depth research on how the central nervous system controls and coordinates muscle organization in Tai Chi remains limited. This study aims to investigate the neuromuscular activity characteristics of Tai Chi athletes and identify optimal muscle synergy patterns. We collected data from 12 high-level Tai Chi athletes using a Vicon motion capture system, Kistler 3D force platform, and Noraxon surface electromyography system, and extracted muscle synergy patterns using Nonnegative Matrix Factorization. Four muscle synergy patterns were estimated in each of the three phases of the leg stirrup movement, with each phase having an optimal synergy pattern (knee lift phase: rectus femoris and vastus lateralis of the right leg; extension phase: rectus femoris, vastus lateralis, biceps femoris, and medial gastrocnemius of the right leg; recovery phase: rectus femoris, vastus lateralis, and medial gastrocnemius of the right leg) explaining the corresponding phase's muscle coordination activities. In conclusion, the optimal muscle synergy patterns for each phase were identified, providing support for the fluidity and power output of the leg stirrup movement, helping Tai Chi athletes to more efficiently exert body strength and maintain balance.